THE EFFECT OF UREA, KCl, SP-36 FERTILIZER ON PRODUCTION AT SOME AGE OF NATURAL RUBBER PLANT (Hevea brasiliensis Mull.Arg): PENGARUH PUPUK UREA,KCl,SP-36 TERHADAP PRODUKSI PADA BEBERAPA UMUR TANAMAN KARET ALAM (Hevea brasiliensis Mull.Arg) - Gebi Hiskia; Akhmad Sopian; Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2022)
Gebi Hiskia Anggraini, Faculty of Agriculture, Widya Gama Mahakam University Samarinda 2020, " The Effect Of Urea, Kcl, Sp-36 Fertilizer On Production At Some Age Of Natural Rubber Plant (Hevea Brasiliensis Mull.Arg)" under the guidance of Mahdalena and Akhmad Sopian. The purpose of this study was to determine the correct dosage of fertilizer to increase the production of natural rubber plants, to determine the effect of rubber plant age and the combination of Urea, KCl, SP-36 fertilizers on increased production,this research was conducted for 3 months, from March 2020 to July 2020. The research location was in a rubber plantation located in Tondoh Village The study used a divided plot design or divided plot consisting of 2 factors with 3 replications, the main plot factor was the age of the rubber plant which consisted of 2 levels of age 8 years and 10 years, the second factor of the sub-plots was Fertilizer consisting of 5 levels, namely: P0 = Without fertilizer, P1 = Urea fertilizer 350 g, KCl 300 g, SP36 260 g / tree, P2 = KCl fertilizer 300 g, SP36 260 g / tree, P3 = Urea fertilizer 350 g, SP36 260 g / tree, P4 = Urea fertilizer 350 g, KCl 300 g / tree The results showed that the application of Urea, KCl, SP-36 fertilizers had a significant effect on latex productivity, latex wet weight, and latex dry weight on the production of rubber (Hevea brasiliensis Muell. Agr). At the age of 8 years and 10 years with the combination of Urea, KCl, SP-36 Fertilizer treatment did not manifest a significant effect on the results of Production, Wet Weight, Dry Weight, and Dry Rubber Content Dry Rubber Content Natural rubber (Hevea brasiliensis Muell. Agr) belongs to quality II which has a low Dry Rubber content that means that the water content in the latex is relatively high Key words: Latex and Inorganic